Pertumbuhan dan Hasil Karabenguk (Mucuna pruriens) sebagai Tanaman Penutup Tanah pada Dua Musim Berbeda - Supriyono Supriyono; Tohari Tohari; Abdul Syukur; Didik Indradewa (Caraka Tani: Journal of Sustainable Agriculture, 2004)
This research does to known: 1) the effect of season, 2) the effect of cover crop kind and organic fertilizer, and 3) the interaction of two factors on growth and yield of velvet bean as cover crops. This research was conducted in Tancep, Ngawen, Gunungkidul at 170 m usl, litosol, 5-17 cm level of soil tillage, 9-10o elevation level, was started at December 2002 and finished at August 2003.This research design was factorial-RCBD, 1st factor was planting season on 2 level, rainy and dry seasons, 2nd factor was cover crop kind on 6 levels, rase and putih gunungkidul velvet bean, Cm and Cp as conventional cover crops, rase and putih gunungkidul with organic fertilizer velvet bean. Per planting hole with 1 plant for velvet bean and 10 plant for coventional cover crop.The result of this research were: 1st, velvet bean growth on rainy season very high than dry season, 2nd vegetative growth rate on velvet bean higher than conventional cover crop, 3rd without fertilizer, velvet bean have some growth and yield comparing by fertilizer velvet bean and 4th some yield variable, dry season was indicated better than rainy season.